A review of mango fruit aroma volatile compounds: State of the art research - Singh, Zora; Lalel, H.; Nair, S. (International Society for Horticultural Science, 2004)
Flavour is comprised of aroma and taste. This paper presents an overview on the fundamental and applied aspects of aroma volatile production in mango fruit with emphasis on the effects of chilling injury and controlled atmosphere (CA) storage. In mango fruit, more than 285 different aroma volatile compounds have been reported which include 7 acids, 55 alcohols, 31 aldehydes, 26 ketones, 14 lactones, 74 esters, 69 hydrocarbons, and 9 other compounds. Aroma volatile compounds have been reported to be influenced by various factors including the mango species, cultivars, location, fruit maturity at harvest, processing, storage and ripening conditions. This review will focus on the effects of various pre and postharvest factors, which regulate aroma volatile production. Our research group have identified sixty one aroma volatile compounds from the 'Kensington Pride' mango fruit pulp, using a head space solid phase microextraction (SPME) technique with gas chromatography (GC) and GC combined with mass spectrophotometry (GC-MS). Low temperatures during storage induced chilling injury and reduced the production of aroma volatile compounds during fruit ripening and in fully ripe fruits. The composition of CA storage as well as storage period affected production of aroma volatile compounds in the pulp of the ripe 'Kensington Pride' and 'Delta R2E2' mangoes.